QR Code Technology Based Laboratory User Attendance to Improve Study Program Governance - Tjahyaningtijas, Hapsari Peni Agustin (INAJEEE (Indonesian Journal of Electrical and Electronics Engineering), 2024)
QR codes are commonly employed in today's technologies. Surabaya State University's Department of Electrical Engineering uses the QR Code to track the presence of Electrical Engineering Laboratory users. hence far, attendance has been taken through manual scanning, hence laboratory members frequently do not take attendance. The usage of the QR Code for attendance has been carried out and tested by scanning the QR code. The QR code direct to google sheet link whereas the Laboratory used to send it to the head of the faculty. The Experiment of using QR Code where held in Telecommunication Laboratory with homogenous area of illumination and scanned at 50 cm, 100 cm, and 150 cm distances. The results demonstrate that QR codes sized 13.5 cm2 can still be scanned at a distance of 100 m but fail at distances greater than 100 cm by using smart phone. The use of QR codes for attendance in the Electrical Engineering Department has numerous advantages, including being efficient in order to establish good governance, efficient, paperless and contributing to a green environment